'Of no sort of use'?: Manuscripts, Memory, and the Family Archive in Eighteenth Century England. (15th March 2023) - Peck, Imogen
ABSTRACT: This article explores the afterlives of manuscripts preserved in the collections of three middling sort families during the long eighteenth century. It foregrounds the role that family archives played in the construction and curation of memory and identity among non-elite families during this period, the intersections between socio-economic status, gender, confessional identity and a subject's curatorial concerns, and the implications for our understanding of archival culture. By showcasing the different ways people engaged with written remains it also demonstrates how reconstructing the motives that underpinned family collections might be possible, offering a framework for the study of intergenerational archival transmission.